Poorly Differentiated Squamous Cell Carcinoma Arising in Tattooed Skin - Deba P. Sarma; Renee B. Dentlinger; Amanda M. Forystek; Todd Stevens; Christopher Huerter (Case Reports in Medicine)
Introduction. Tattoos have increasingly become accepted by mainstream Western society. As a result, the incidence of tattoo-associated dermatoses is on the rise. The presence of a poorly differentiated squamous cell carcinoma in an old tattooed skin is of interest as it has not been previously documented. Case Presentation. A 79-year-old white homeless man of European descent presented to the dermatology clinic with a painless raised nodule on his left forearm arising in a tattooed area. A biopsy of the lesion revealed a poorly differentiated squamous cell carcinoma infiltrating into a tattoo. The lesion was completely excised and the patient remains disease-free one year later. Conclusion. All previous reports of squamous cell carcinomas arising in tattoos have been well-differentiated low-grade type or keratoacanthoma-type and are considered to be coincidental rather than related to any carcinogenic effect of the tattoo pigments. Tattoo-associated poorly differentiated invasive carcinoma appears to be extremely rare.